2009
DOI: 10.1007/s10649-009-9197-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cooperative learning on preschoolers’ mathematics problem-solving ability

Abstract: The aim of this study is to investigate the efficiency of cooperative learning on preschoolers' verbal mathematics problem-solving abilities and to present the observational findings of the related processes and the teachers' perspectives about the application of the program. Two experimental groups and one control group participated in the study. Results found that preschoolers in the experimental groups experienced larger improvements in their problem-solving abilities than those in the control group. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 9 publications
2
26
0
8
Order By: Relevance
“…More opportunities should be given to discussion, problem solving, creating solutions and working with peers. Several educators in the field of mathematics education conducted studies using cooperative learning and found increase in students' mathematics achievement (Brush, 1997;Isik and Tarim, 2009;Nichols and Miller, 1994;Tarim, 2009;Tarim and Akdeniz, 2008). Shimazoe and Aldrich (2010) provides several benefits on the use of cooperative learning approach for students.…”
Section: Introductionmentioning
confidence: 99%
“…More opportunities should be given to discussion, problem solving, creating solutions and working with peers. Several educators in the field of mathematics education conducted studies using cooperative learning and found increase in students' mathematics achievement (Brush, 1997;Isik and Tarim, 2009;Nichols and Miller, 1994;Tarim, 2009;Tarim and Akdeniz, 2008). Shimazoe and Aldrich (2010) provides several benefits on the use of cooperative learning approach for students.…”
Section: Introductionmentioning
confidence: 99%
“…One main purpose of mathematics education is to help students think mathematically (Ding et al, 2007) and this can be achieved by facilitating problem solving within a cooperative learning environment (Tarim, 2009). In this sense, cooperative learning activities such as group work and discussion in terms of developing a capability for using and applying knowledge, reasoning, and cognitive understanding are more important than memorization of facts and mastery of routine skills in mathematics education (Atagi, 2002).…”
Section: Cooperative Learning: Theoretical Antecedents and Mathematicmentioning
confidence: 99%
“…Puacharearn and Fisher (2004) also found that even though it is difficult to change the Thai classroom environments, the successful implementation of cooperative learning strategies could be achieved in Thai schools if Thai teachers are provided with sound frameworks to inform their use of cooperative learning. Some research showed that cooperative learning in mathematics in Asian education environments improves problem solving and increases students' engagement (Tarim, 2009). In sum up, the extreme contrast implies that the best selection from the models for Asian culture is meaningless.…”
Section: Affinity Research Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Dees (1991) comparou o desempenho de grupos cooperativos e colaborativos de estudantes de graduação na solução de problema de matemática, demonstrando que os grupos cooperativos tiveram um desempenho maior. Tarim (2009) realizou um estudo com 54 crianças com idades de 5 a 6 anos de escolas privadas da Turquia e constatou que os grupos cooperativos tiveram um desempenho significativamente maior na solução de problemas de matemática do que os alunos que resolveram problemas de maneira individual ou em grupos colaborativos. Estes estudos indicam, portanto, que a aprendizagem cooperativa favorece a solução de problemas quando comparada a estratégias colaborativas ou individuais.…”
Section: Introductionunclassified